192k views
21 votes
Solve for x ~

x {}^(2) - 5x + 6 = 0

thankyou ~​

User Abrunet
by
5.7k points

2 Answers

10 votes


x^2 -5x +6 =0\\\\\implies x^2 -3x -2x +6 = 0\\\\\implies x(x-3) -2(x-3) =0\\\\\implies (x-3)(x-2)=0\\\\\implies x =3, ~ x = 2

User David Saltares
by
5.1k points
7 votes

Answer:

The value of x = 2 or 3

Explanation:

By factorisation ,

=> x² - 5x + 6 =0

=> x² - 3x - 2x + 6 = 0

=> x ( x-3 ) -2 ( x-3 ) = 0

=> (x-2) (x-3) = 0

so, the value of x = 3 or 2

User Aayush Anand
by
5.1k points